Implementation of Total Quality Management (TQM): Optimizing School Branding Strategy in Urban Islamic Schools - Hendra Kurniawan; Syamsul Arifin; Mulyono Mulyono (STAI Hubbulwathan Duri, 2024)
Islam Terpadu Schools and Islam Unggulan Schools have emerged as alternative educational models combining Islamic and modern education. These institutions aim to strengthen religious foundations, build character, and enhance digital capabilities, addressing contemporary educational challenges. This qualitative study examines the school branding strategies of Islam Terpadu High School Al Fityan and Islam High School Al Amjad in Medan. Data collection methods included observations, interviews, and document analysis, involving key stakeholders such as school foundations, administrators, students, the community, and the JSIT (Jaringan Sekolah Islam Terpadu) network in North Sumatra. The analysis integrates Total Quality Management principles to contextualize branding efforts. Al Fityan High School employs the